Answer:
The cost of one adult ticket is $13, and the price of one student ticket is $4.
Step-by-step explanation:
This question can be solved using a system of equations.
I am going to say that:
x is the cost of an adult ticket
y is the cost of a student ticket.
6 adult tickets and 1 student ticket for a total of $82
This means that
![6x + y = 82](https://tex.z-dn.net/?f=6x%20%2B%20y%20%3D%2082)
![y = 82 - 6x](https://tex.z-dn.net/?f=y%20%3D%2082%20-%206x)
The school took in $51 on the second day by selling 3 adult tickets and 3 student tickets.
This means that
![3x + 3y = 51](https://tex.z-dn.net/?f=3x%20%2B%203y%20%3D%2051)
Simplifying by 3
![x + y = 17](https://tex.z-dn.net/?f=x%20%2B%20y%20%3D%2017)
Since ![y = 82 - 6x](https://tex.z-dn.net/?f=y%20%3D%2082%20-%206x)
![x + 82 - 6x = 17](https://tex.z-dn.net/?f=x%20%2B%2082%20-%206x%20%3D%2017)
![-5x = -65](https://tex.z-dn.net/?f=-5x%20%3D%20-65)
![5x = 65](https://tex.z-dn.net/?f=5x%20%3D%2065)
![x = \frac{65}{5} = 13](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B65%7D%7B5%7D%20%3D%2013)
![y = 82 - 6x = 82 - 6*13 = 82-78 = 4](https://tex.z-dn.net/?f=y%20%3D%2082%20-%206x%20%3D%2082%20-%206%2A13%20%3D%2082-78%20%3D%204)
The cost of one adult ticket is $13, and the price of one student ticket is $4.
Answer:
-54, 162, -486
Step-by-step explanation:
You multiply the number in front by -3.
2*-3=-6
-6*-3=18
18*-3=-54
-54*-3=162
162*-3=-486
-Please mark as brainliest!-
-Hope this helps!-
-Good Luck!-
Answer:
![\boxed{ \sf x=\dfrac{4\pm\sqrt{43}}{2}}](https://tex.z-dn.net/?f=%5Cboxed%7B%20%5Csf%20x%3D%5Cdfrac%7B4%5Cpm%5Csqrt%7B43%7D%7D%7B2%7D%7D)
Explanation:
![\rightarrow \sf \dfrac{1}{x-5}+\dfrac{3}{x+2}=4](https://tex.z-dn.net/?f=%5Crightarrow%20%5Csf%20%5Cdfrac%7B1%7D%7Bx-5%7D%2B%5Cdfrac%7B3%7D%7Bx%2B2%7D%3D4)
<u>make the denominators same</u>
![\rightarrow \sf \dfrac{1(x+2)}{(x-5)(x+2)}+\dfrac{3(x-5)}{(x+2)(x-5)}=4](https://tex.z-dn.net/?f=%5Crightarrow%20%5Csf%20%5Cdfrac%7B1%28x%2B2%29%7D%7B%28x-5%29%28x%2B2%29%7D%2B%5Cdfrac%7B3%28x-5%29%7D%7B%28x%2B2%29%28x-5%29%7D%3D4)
<u>join the fractions together</u>
![\rightarrow \sf \dfrac{x+2+3x-15}{(x-5)(x+2)}=4](https://tex.z-dn.net/?f=%5Crightarrow%20%5Csf%20%5Cdfrac%7Bx%2B2%2B3x-15%7D%7B%28x-5%29%28x%2B2%29%7D%3D4)
<u>cross multiply</u>
![\rightarrow \sf x+2+3x-15=4(x-5)(x+2)](https://tex.z-dn.net/?f=%5Crightarrow%20%5Csf%20x%2B2%2B3x-15%3D4%28x-5%29%28x%2B2%29)
<u>simplify</u>
![\rightarrow \sf 4x-13=4x^2-12x-40](https://tex.z-dn.net/?f=%5Crightarrow%20%5Csf%204x-13%3D4x%5E2-12x-40)
<u>group the variables</u>
![\rightarrow \sf 4x^2-16x-27 = 0](https://tex.z-dn.net/?f=%5Crightarrow%20%5Csf%204x%5E2-16x-27%20%3D%200)
<u>use quadratic formula</u>
![\rightarrow \sf x = \dfrac{-\left(-16\right)\pm \sqrt{\left(-16\right)^2-4\cdot \:4\left(-27\right)}}{2\cdot \:4}](https://tex.z-dn.net/?f=%5Crightarrow%20%5Csf%20x%20%3D%20%5Cdfrac%7B-%5Cleft%28-16%5Cright%29%5Cpm%20%5Csqrt%7B%5Cleft%28-16%5Cright%29%5E2-4%5Ccdot%20%5C%3A4%5Cleft%28-27%5Cright%29%7D%7D%7B2%5Ccdot%20%5C%3A4%7D)
<u>simplify the following</u>
![\rightarrow \sf x=\dfrac{4\pm\sqrt{43}}{2}](https://tex.z-dn.net/?f=%5Crightarrow%20%5Csf%20x%3D%5Cdfrac%7B4%5Cpm%5Csqrt%7B43%7D%7D%7B2%7D)
Answer:
3
Step-by-step explanation:
First, find the midline by averaging the highest value (2) and the lowest value (-4). In other words, do (2+-4)/2. You get the midline as -1. Now find the distance from the midline to the top. Distance from -1 to 2 is 3. Amplitude is therefore 3.
Add them together and subtracct thee total.